Clinical presentation and investigation of patients proceeding to isotope lung scanning for suspected pulmonary embolism. Issue 774 (April 1990) - Fennerty, A. G.; Shetty, H. G.; Paton, D.; Roberts, G.; Routledge, P. A.; Campbell, I. A.
Abstract : The presenting features of 250 consecutive patients who underwent a ventilation/perfusion lung scan for suspected pulmonary embolus (PE) were analysed. Ninety-six patients had lung scans highly suggestive of PE, with one or more unmatched segmental perfusion defects (scan positive), 86 had low probability scans (scan negative) and 68 an indeterminate scan. Scan positive patients were more likely to have a PaO2 of less than 10.7 kPa, an elevated P(A-a)O2 and an abnormal chest X-ray compared with scan negative patients but these measurements were of poor specificity. Furthermore, scan-positive patients had a higher incidence of lung disease. Localized chest wall tenderness was more common in scan-positive patients, occurring in 9% of patients, but there were no other significant differences in individual symptoms, signs or electrocardiographic findings between scan-positive and scan-negative patients. The diagnosis of PE should not be made on clinical grounds alone and all patients suspected of having a PE should at least undergo isotope lung scanning.